Deficiency of Carbonic Anhydrase II Results in a Urinary Concentrating Defect - Krishnan, Devishree; Pan, Wanling; Beggs, Megan R.; Trepiccione, Francesco; Chambrey, Régine; Eladari, Dominique; Cordat, Emmanuelle; Dimke, Henrik; Alexander, R. Todd (Frontiers in Physiology, 2018)
Carbonic anhydrase II (CAII) is expressed along the nephron where it interacts with a number of transport proteins augmenting their activity. Aquaporin-1 (AQP1) interacts with CAII to increase water flux through the water channel. Both CAII and aquaporin-1 are expressed in the thin descending limb; however, the physiological role of a CAII-AQP1 interaction in this nephron segment is not known. To determine if CAII was required for urinary concentration, we studied water handling in CAII-deficient mice. CAII-deficient mice demonstrate polyuria and polydipsia as well as an alkaline urine and bicarbonaturia, consistent with a type III renal tubular acidosis. Natriuresis and hypercalciuria cause polyuria, however, CAII-deficient mice did not have increased urinary sodium nor calcium excretion. Further examination revealed dilute urine in the CAII-deficient mice. Urinary concentration remained reduced in CAII-deficient mice relative to wild-type animals even after water deprivation. The renal expression and localization by light microscopy of NKCC2 and aquaporin-2 was not altered. However, CAII-deficient mice had increased renal AQP1 expression. CAII associates with and increases water flux through aquaporin-1. Water flux through aquaporin-1 in the thin descending limb (TDL) of the loop of Henle is essential to the concentration of urine, as this is required to generate a concentrated medullary interstitium. We therefore measured cortical and medullary interstitial concentration in wild-type and CAII-deficient mice. Mice lacking CAII had equivalent cortical interstitial osmolarity to wild-type mice: however, they had reduced medullary interstitial osmolarity. We propose therefore that reduced water flux through aquaporin-1 in the TDL in the absence of CAII prevents the generation of a maximally concentrated medullary interstitium. This, in turn, limits urinary concentration in CAII deficient mice.